Cardiovascular nursing physiologic anatomy (Baltimore : Williams & Wilkins Electronic Media, 1992)
This video reviews the anatomy and physiology of the cardiovascular system, looking at normal cardiac function and causes of abnormalities. It shows the cardiac conduction system and examines variables affecting left ventricular function
The Williams & Wilkins Essentials of Critical Care Video Library
Keywords: Cardiovascular diseases -- Nursing; Anatomy